(untitled) (PENDAIS, 2025)
This article aims to explore holistic education from the perspective of Islamic philosophy. The method employed is qualitative descriptive analysis, gathering references from relevant articles and books. The research findings and discussions indicate that a holistic approach, encompassing physical, mental, emotional, and spiritual aspects, can encourage individuals to achieve balance and optimal development. The discussion on Islamic values emphasizes the importance of character and ethical development in education, which focuses not only on academic achievement but also on the formation of a well-rounded personality. By applying the principles of holistic education, it is hoped that individuals can maximize their potential, resulting in a generation that is not only intellectually capable but also morally upright and socially responsible.